2021
DOI: 10.1177/1356766721995973
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the source credibility of Instagram influencers on travel intention: The mediating role of parasocial interaction

Abstract: The primary objective of this study is to determine the impact of the sub-dimensions of source credibility (attractiveness, trustworthiness and expertise), and its secondary objective is to investigate the mediating role of parasocial interaction the effect of the sub-dimensions of source credibility on travel intention. The study was conducted with data obtained from 379 participants and the response rate was found to be 88%. The validity and credibility of the constructs were tested through confirmatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 65 publications
(40 reference statements)
3
43
0
17
Order By: Relevance
“…From the uncertainty reduction theory perspective in the social-psychological field, this study established and verified the influence relationship between credibility from the marketing field and para-social relationship from the media psychology field. The finding of this study is consistent with the findings of prior studies (Yuan et al, 2016;Zhang et al, 2020;Yılmazdogan et al, 2021). Moreover, this study further clarifies the underlying reason of this relationship, which indicated that a credible endorser could reduce the uncertainty of potential tourists which would facilitate the potential tourists building a para-social relationship with the endorser.…”
Section: Discussion and Conclusion Theoretical Implicationssupporting
confidence: 91%
See 2 more Smart Citations
“…From the uncertainty reduction theory perspective in the social-psychological field, this study established and verified the influence relationship between credibility from the marketing field and para-social relationship from the media psychology field. The finding of this study is consistent with the findings of prior studies (Yuan et al, 2016;Zhang et al, 2020;Yılmazdogan et al, 2021). Moreover, this study further clarifies the underlying reason of this relationship, which indicated that a credible endorser could reduce the uncertainty of potential tourists which would facilitate the potential tourists building a para-social relationship with the endorser.…”
Section: Discussion and Conclusion Theoretical Implicationssupporting
confidence: 91%
“…Zhang et al (2020) found that the three sub-dimensions of credibility significantly influence the PSR of receivers with a celebrity. In the social media context, Yılmazdogan et al (2021) proved the same result. Based on the above theoretical perspective and empirical evidence, H2: The credibility of the endorser has a positive impact on the para-social relationship of potential tourists with the endorser.…”
Section: Endorser Credibility and Para-social Relationshipsmentioning
confidence: 54%
See 1 more Smart Citation
“…Theoretically, this work makes several significant contributions to academia. Firstly, we adopted the source credibity model to verity the relationship among attractiveness, trustworthiness, expertise, parasocial relationships, destination attitude and visit intention, giving empirical support to the existing literature [ 72 74 , 81 , 82 , 104 ]. Secondly, although previous literatures showed that endorsers in destination marketing received considerable amount of academic attention, literature about the influence mechanism of endorsers’ credibility on tourist visit intention and destination attitude remains extremely limited.…”
Section: Theoretical and Practical Implicationmentioning
confidence: 81%
“…Food vlog is a niche form of travel vlogs that highlights travel expeditions to the destinations around their cultural delicacies and culinary specialties. If digital influencers are perceived to develop creditability in a specific sectorial field, for example, food vlogging, then they begin to influence the behaviors of their followers in that domain (Yılmazdo gan et al, 2021;Mariani et al, 2021). Not all digital influencers are equally effective in achieving this outcome, as the literature alludes to three important stimulus characteristics, that is, perceived similarity with the source (Lee and Watkins, 2016;Mainolfi et al, 2022), source Food vloggers and parasocial interactions trustworthiness (Kim et al, 2014) and source expertise (Li et al, 2022) that can determine the extent to which messages transmitted by these digital influencers would affect the viewers.…”
Section: Theoretical Backdropmentioning
confidence: 99%